Dinamika Organisasi Lembaga Pendidikan Islam Muhammadiyah - Latifah, Ami; Hasan, Shohib; Warisno, Andi; Ansori, M Afif; Andari, An An (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This article discusses the organizational dynamics of Muhammadiyah Islamic educational institutions. The purpose of this study is to find out how changes occur in the organization of Muhammadiyah Islamic educational institutions, including the factors that influence them and the programs developed to improve the quality and effectiveness of the education offered. Through socio-historical analysis with a historiographical approach, the factors influencing the development of this educational institution were identified, including political policies, social and cultural changes, technological developments, and Muhammadiyah’s educational thoughts and movements. Development programs developed to improve the quality of education are also reviewed, such as curriculum development, human resources, facilities and infrastructure, learning methods and technology, and cooperation with other educational institutions. The results of this study are that there are four dynamic periods of educational development in the Muhammadiyah organization, namely the pioneer period (1900-1923), the development period (1923-1/970), the development period (1923-1970), the institutionalization period (1970-1998), and the transformation period. (1998-present). In the 1970s, the development of Islamic education in the Muhammadiyah body began with the establishment of schools plus religion, which became the forerunner to the establishment of the Muhammadiyah Islamic Boarding School.